Kecenderungan Narsistik ditinjau dari Kesepian pada Mahasiswi Pengguna Jejaring Sosial Media Instagram Fakultas Ekonomi Universitas Prima Indonesia - Fani Natasya; Vion Vion; Susi Anjelika; Heryanto Heryanto (Psyche 165 Journal, 2020)
This study aims to determine the relationship between lonely with narcissistic tendencies. The hypothesis of this study states that there is a negative relationship between lonely with narcissistic tendencies, assuming that the higher the lonely is, the lower the narcissistic tendencies, and conversely the lower the lonely is, the higher the narcissistic tendencies will be. The subjects of this study were 256 college students of Universitas Prima Indonesia. Datas were obtained from scales used to measure turnover intention and work stress. Calculations were performed by testing the analysis requirements (assumption) that consisted of tests for normality and linearity. The data were analyzed using Product Moment Correlation with SPSS 20 for Windows. The results of the data analysis showed that the correlation coefficient was – 0,414 with a significance value of 0.000 (p <0.05). It showed that there is a negative relationship between lonely and narcissistic tendencies. The results of this study indicate that the contributions made by the variable of work stress on turnover intention was 17,2 percent, while the remaining 82,8 percent was influenced by other factors that were not examined. From these results, it is concluded that the hypothesis, which stated that there is a negative relationship between the lonely and narcissistic tendencies, is acceptable.